Political Conflict in the Umayyad Era (661-1031 AD) - Afifah, Shery Fara; Ariyanti, Nova; Umam, Khoirul Safril; Aini, Nurul; Mubaraq, Zulfi; Kholil, Ahmad (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
The study of conflict in the Umayyad era is very important to be studied in more depth. This is because the study never stops being debated. The purpose of this paper is to understand 3 things: First, the paradigm of political conflict  in the Umayyad era. Second, internal and external factors that influenced political conflict  in the Umayyad era. Third, the positive and negative implications of political conflict  in the Umayyad era on Islamic society. The method used is qualitative research with a library research approach. The results found 3 things: First, there are 6 forms of paradigm: (1) Conflict (2) Resistance (3) Struggle (4) Feud (5) Transfer of power (6) Violence and deceit. Second, internally, there are 6 factors that influence political conflict  in the Umayyad era: (1) Leadership incompetence (2) Government system (3) Expansion of power (4) Equality of interest (5) Political interests (6) Leadership principles. Externally, there are 2 factors that influence: (1) Political pressure (2) Invasion from other countries. Third, there are 5 positive implications for muslims: (1) Military strength (2) Territorial expansion (3) Administrative institutions (4) Lighthouse of world civilization (5) Official language. Meanwhile, there are 3 negative implications: (1) The collapse of power (2) The growth of Muslims was hampered (3) Fierce debate arose. The conclusion of this article shows that it provides new insights and views on political conflict in the Umayyad era.